Semut Subfamili Myrmicinae di Suaka Alam Maninjau Utara Selatan, Kabupaten Agam, Sumatera Barat - Susan Septriani; Henny Herwina; Mairawita Mairawita (Jurnal Biologi Universitas Andalas, 2015)
Research about inventory of ants Myrmicinae (Hymenoptera: Formicidae) in Nature Reserve Maninjau Utara-Selatan, Agam, West Sumatra was conducted from June to December 2015 by using the "Quadra protocol" which consist of a combination of four methods:  free collection, leaf litter sampling, soil sampling, honey  bait. A total of 19 species, 9 genera, 5 tribe were collected. Pheidole was found as genus with the highest number of species (9 species), followed by Crematogaster (3 species).